A Unified Theory of China's Three-Pillar Pension System - Ming Gao; Zexin Wei; Haotian Xiang (《中国社会科学》（英文版）Social Sciences in China, 2025)
This paper develops a unified theory integrating the three pillars of the pension system—public, occupational, and private pensions—within a heterogeneous-agent overlapping generations (OLG) model. By incorporating income heterogeneity and institutional features unique to each pillar, the model captures how individuals across the income distribution participate in the pension system and derive utility. We characterize the distinct yet interactive roles of each pillar in providing risk sharing and retirement security and identify fundamental trade-offs in pension design. Our model provides a laboratory for analyzing the coordination of the three pillars that aims at enhancing equity and fiscal sustainability.